High systemic immune-inflammation index predicts poor prognosis in advanced lung adenocarcinoma patients treated with EGFR-TKIs. Issue 33 (August 2019) - Deng, Chao; Zhang, Na; Wang, Yapeng; Jiang, Shun; Lu, Min; Huang, Yan; Ma, Jin'an; Hu, Chunhong; Hou, Tao
Abstract : Abstract: EGFR-TKIs have been widely used in the first-line treatment of NSCLC patients harboring EGFR mutations. However, the prognosis indicators are limited. In the present study, the prognostic value of systemic immune-inflammation index (SII), neutrophil to lymphocyte ratio (NLR), and platelet to lymphocyte ratio (PLR) were assessed in EGFR-Mutant lung adenocarcinoma patients treated with first-generation EGFR-TKIs. Two hundred three patients were included in this retrospective analysis. SII was calculated as platelet counts × neutrophil counts / lymphocyte counts. Receiver operating characteristic (ROC) curve was used to evaluate the optimal cut-off value for SII, NLR, and PLR. Univariate and multivariate survival analysis were performed to identify factors correlated with PFS and OS. Applying cut-offs of ≥1066.935 (SII), ≥4.40 (NLR), and ≥182.595 (PLR), higher NLR was associated with worse Eastern Cooperative Oncology Group performance status (ECOG PS) ( P  = .006), and higher brain metastasis rate ( P  = .03), higher PLR was associated with smoking history ( P  = .037), and worse ECOG PS ( P  = .001), and higher SII groups were associated with worse ECOG PS ( P  = .002). In univariate analysis, higher NLR ( P  < .001), higher PLR ( P  = .002), and higher SII ( P  < .001) were associated with worse PFS. Higher NLR ( P  < .001), and higher SII ( P  < .001) were associated with worse OS. In multivariate analysis, NLR (HR 1.736;95%CI:1.020–2.954; P  = .03), PLR (HR 1.823; 95%CI:1.059–3.137; P  = .04), and SII (HR2.577; 95%CI:1.677–3.958; P  < .001) were independently correlated with PFS. While only SII (HR 2.802; 95%CI:1.659–4.733; P  < .001) was independently correlated with OS. The present study demonstrated that SII is an independent prognostic factor for poor survival of advanced EGFR-Mutant lung adenocarcinoma patients treated with first-generation TKIs.